2018
DOI: 10.1002/term.2739
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell colony interspacing effect on differentiation to neural cells

Abstract: Efforts to enhance the efficiency of neural differentiation of stem cells are primarily focused on exogenous modulation of physical niche parameters such as surface topography and extracellular matrix proteins, or addition of certain growth factors or small molecules to culture media. We report a novel neurogenic niche to enhance the neural differentiation of embryonic stem cells (ESCs) without any external intervention by micropatterning ESCs into spatially organized colonies of controlled size and interspaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…The first use was with noncontact printing of embryonic stem cells onto support cells that induce differentiation (13). This has since been expanded to show that spacing between cell colonies can have a profound effect on differentiation (134). Tissue constructs can be formed using ATPSs, in analogy to cell sheets used in tissue engineering.…”
Section: Cell Patterningmentioning
confidence: 99%
“…The first use was with noncontact printing of embryonic stem cells onto support cells that induce differentiation (13). This has since been expanded to show that spacing between cell colonies can have a profound effect on differentiation (134). Tissue constructs can be formed using ATPSs, in analogy to cell sheets used in tissue engineering.…”
Section: Cell Patterningmentioning
confidence: 99%
“…Alternatively, several studies have reported the use of PA6, a stromal cell line derived from mouse skull bone marrow, immersed in the PEG phase in which DEX droplets containing stem cells are printed to differentiate them into neural cells, demonstrating that by having direct contact with PA6 cells is sufficient to induce neural differentiation without the addition of external factors 21,30–33 …”
Section: Neuronal Cell Differentiation Using Atps‐3d Culturesmentioning
confidence: 99%
“…31 Alternatively, several studies have reported the use of PA6, a stromal cell line derived from mouse skull bone marrow, immersed in the PEG phase in which DEX droplets containing stem cells are printed to differentiate them into neural cells, demonstrating that by having direct contact with PA6 cells is sufficient to induce neural differentiation without the addition of external factors. 21,[30][31][32][33] Cell density, colony size and interconnectivity are geometrical parameters to consider during the construction of 3D cultures (Fig. 2) to enhance cell survival, migration, neurite outgrowth and lineage commitment.…”
Section: Neuronal Cell Differentiation Using Atps-3d Culturesmentioning
confidence: 99%
See 2 more Smart Citations